Evaluation of Genotoxic and Cytotoxic Effects in Human Peripheral Blood Lymphocytes Exposed In Vitro to Neonicotinoid Insecticides News - María Elena Calderón-Segura; Sandra Gómez-Arroyo; Rafael Villalobos-Pietrini; Carmen Martínez-Valenzuela; Yolanda Carbajal-López; María del Carmen Calderón-Ezquerro; Josefina Cortés-Eslava; Rocío García-Martínez; Diana Flores-Ramírez; María Isabel Rodríguez-Romero; Patricia Méndez-Pérez; Enrique Bañuelos-Ruíz (Journal of Toxicology)
Calypso (thiacloprid), Poncho (clothianidin), Gaucho (imidacloprid), and Jade (imidacloprid) are commercial neonicotinoid insecticides, a new class of agrochemicals in México. However, genotoxic and cytotoxic studies have not been performed. In the present study, human peripheral blood lymphocytes (PBL) were exposed in vitro to different concentrations of the four insecticides. The genotoxic and cytotoxic effects were evaluated using the alkaline comet and trypan blue dye exclusion assays. DNA damage was evaluated using two genotoxicity parameters: tail length and comet frequency. Exposure to 9.5×10-6 to 5.7×10-5 M Jade; 2.8×10-4 to 1.7×10-3 M Gaucho; 0.6×10-1 to 1.4×10-1 M Calypso; 1.2×10-1 to 9.5×10-1 M Poncho for 2 h induced a significant increase DNA damage with a concentration-dependent relationship. Jade was the most genotoxic of the four insecticides studied. Cytotoxicity was observed in cells exposed to 18×10-3 M Jade, 2.0×10-3 M Gaucho, 2.0×10-1 M Calypso, 1.07 M Poncho, and cell death occurred at 30×10-3 M Jade, 3.3×10-3 M Gaucho, 2.8×10-1 M Calypso, and 1.42 M Poncho. This study provides the first report of genotoxic and cytotoxic effects in PBL following in vitro exposure to commercial neonicotinoid insecticides.